A study of post-dated pregnancy with special reference to maternal and perinatal outcome in nulliparous women - Karmakar, Shreyasi; Bid, Sabyasachi; Maiti, Tapan Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The study was aimed to determine the mode of delivery, maternal outcome and perinatal outcome in prolonged pregnancy. Methods: It was a prospective observational study. Uncomplicated nulliparous singleton pregnancies who have completed 37 weeks of gestation were included in the study. Inclusion and exclusion criteria were strictly followed. Total 200 cases were divided into study group and control group. Those who have crossed their Estimated date of delivery (EDD) were compared with term pregnancies (not crossed their EDD). Results: The study group and control group consist of 114 and 86 women respectively. The incidence of caesarean section (64.04%), induction of labour (50.88%) is significantly higher in the study group. It also shows that the occurrence of caesarean section (63.79%) is more in post-dated pregnant women who underwent induction of labour. The most common indication for caesarean section was fetal distress in both groups. The commonest maternal complication was prolonged labour and perinatal complication was fetal distress in both groups. The incidence of low birth weight was significantly less in post-dated pregnancy. Conclusions: Our study suggests that the incidence of induction of labour and caesarean section is significantly higher in post-dated pregnancy. Although the mean birth weight baby is more in them, a definite policy should be recommended for optimum timing of intervention to avoid maternal and perinatal complications.